NÅR „PENGE“ ER ANDET OG MERE END PENGE: Røde fjerruller på Reef Øerne - Pinholdt, Jens (Tidsskriftet Antropologi, 2018)
Until the middle of the 20th century red feather rolls were an important and highly visible aspect of social life in the the Northern Santa Cruz Islands comprising Nendö, Reef Islands and Duff Islands. These rolls, commonly but misleadingly known and referred to as “red feather money” even in anthropological literature, by the 1970s had nearly gone out of use and by the 1990s they had disappeared. In this historical reconstruction the red feather rolls are viewed in their heyday in their regional as well as their local social context. The ethnographic knowledge behind the reconstruction is based on all the available sources of the precolonial and colonial periods, the major anthropological analyses of the 1960s and the 1970s and my own fieldwork data established after 1973. The anthropological analysis of the material takes guidance from Maurice Godelier (1978) who points out that valuables in primitive society often have a dual character, they are both commodities and gifts; and from Kajsa Ekholm (1978) who states that power relations in tribal societies are largely established, consolidated and maintained through the control of valuables. Red feather rolls played an important part in the regional trading system connecting the Northern Santa Cruz Islands. This peculiar form of valuable was only produced in the rich central island of Nendö from where it was taken to the more marginal islands as part of the inter-island trading, usually in exchange of women. The big trading canoes were only built in the Duff Islands and had to be for paid in red feather rolls. They were owned and sailed by the leading big-men in the Western Reef Islands who accordingly were able to exercise considerable control over the influx and the flow internally of the feather rolls. Feather rolls were indispensable in the gift-exchanges accompanying all major social ceremonies and events such as bridewealth, compensations and life-cycle ceremonies. So a generous local big-man could use his feather rolls for the benefit of his relatives and favoured friends who were in need of it, and at the same time he would make them into his loyal supporters. In this social system, control of the unique valuable was the major road to respect and influence, even to power, for the big-man. The red feather rolls were part of an intricate local social order which depended for its reproduction on the regional trading system. But all this had to disappear when market economy based on western money, Christian influence, and colonial control took over. The regional trading system collapsed; the red feather rolls lost their significance and the big-men the base of their power.